Back to basics with distal thumb reconstruction. Easy management of the incomplete amputation. Issue 6 (3rd July 2021) - Losco, L; Kaciulyte, J; Delia, G; Bolletta, A; Lo Torto, Federico; Di Taranto, G; Ribuffo, D; Cigna, E
Abstract: Thumb reconstruction has always been challenging for hand surgeons. The disability can severely influence the working and social life of the patient, even if just the distal phalanx is affected. Revascularization is the best surgical option for incomplete distal amputation, although microsurgical reconstruction, sometimes, could be not feasible. A simple basic-skills-based reconstructive method, that takes into account the length preservation and a short recovery should be advocated. We treated 14 incomplete distal thumb amputations with bone exposure, classified as Hirase zone IIA-IIB. The distal thumb was held by a short tissue islet, nor neurovascular bundle, nor dorsal vein was included. Patients were assessed for skin and bone healing, length of thumb shortening, and time of return to full occupational activity. QDASH score was evaluated along with a two-point discrimination test. The outcome was fair in all 14 patients. Partial distal thumb necrosis was observed in six cases (40%); they healed by secondary intention. Finger shortening had a mean of 6.9 mm (range, 6–8 mm), mean interphalangeal joint motion was 48 degrees (range, 45–55 degrees). The median static two-point discrimination was 7.1 mm (range, 6–9 mm), the mean quick DASH score was 1.8 (range, 0–4.5). All patients returned to work within a mean of 4.3 weeks (range, 4–5 weeks). The follow-up period was 12 months. Length preservation, fast recovery and easy return to manual work, above all, are the keystones of our successful procedure. Whether the revascularization is not executable, we provide a reliable and simple method to grant a functional thumb.